BILINGUAL TOURIST POCKET BOOK USING QR CODE FOR TOURISTS AT MAIMUN PALACE TO INTRODUCE THE CULTURE AND HERITAGE OF THE DELI SULTANATE - Agustina, Ika; Andrian, Andrian; Lubis, Reniwati (International Journal of Multidisciplinary Research and Literature, 2024)
The use of digital technology in tourism development can provide major benefits for visitors, local communities and stakeholders tourist. However, it is important to integrate technology wisely and paying attention to the unique needs of each tourist destination. In Medan, there is a tourist site in the form of a palace, namely the Maimun Palace, a legacy of the Deli Sultanate. Access information about Maimun Palace and the historical objects contained in it still felt limited for visitors. Therefore, a deep breakthrough is needed eliminates this limitation. Bilingual travel pocket book with QR Code for travelers is a good idea to provide easily accessible information and useful for visitors. With a bilingual travel pocketbook equipped with a QR Code, visitors will be able to easily access the information they need to make their travel experience more informative and memorable. Therefore, this research aims to developing a Bilingual Travel Pocket Book using QR Code for tourists at Maimun Palace. The research method implemented in this study is Research & Development. Every relic of the Kingdom era that is tangible and intangibles are research objects while the research subjects in this study are domestic and foreign tourists. The data collection technique in this research is Deli Sultanate archival documentation, literary studies, and interviews with the representative of Sultan Ma’moen Al Rasyid Foundation. This research produces a travel pocket book bilingual in digital form with a QR code that can provide information to domestics and tourists abroad regarding the history, culture, and heritage of the Deli Sultanate